Spontaneous dissociation and dislocation of retisert pellet - Akduman, Levent; Becker, Matthias D.; Mackensen, Friederike (Ocular immunology and inflammation, 2013)
Purpose: To report 4 cases of spontaneous Retisert pellet dislocation. Design: Retrospective case series. Methods: Description of cases. Results: In all 4 cases, the time of Retisert implantation was 3-6 years prior to presentation. One case was complicated by retinal commotio and a retinal tear; another was complicated by corneal endothelial failure, due to dislocation of the pellet into the anterior chamber. Conclusion: Spontaneous pellet separation may occur with Retisert as a late complication. It is unclear whether these dislocations are from a manufacturing fault or are related to extended intraocular exposure.